The A-C linker controls centriole structural integrity and duplication - Lorène Bournonville; Marine. H. Laporte; Susanne Borgers; Paul Guichard; Virginie Hamel (Nature Communications)
Abstract Centrioles are evolutionarily conserved barrel-shaped organelles playing crucial roles in cell division and ciliogenesis. These functions are underpinned by specific structural sub-elements whose functions have been under investigation since many years. The A-C linker structure, connecting adjacent microtubule triplets in the proximal region, has remained unexplored due to its unknown composition. Here, using ultrastructure expansion microscopy, we characterized two recently identified A-C linker proteins, CCDC77 and WDR67, and discovered MIIP as an additional A-C linker protein. Our findings reveal that these proteins localize between microtubule triplets at the A-C linker, forming a complex. Depletion of A-C linker components disrupt microtubule triplet cohesion, leading to breakage at the proximal end. Co-removal of the A-C linker and the inner scaffold demonstrates their joint role in maintaining centriole architecture. Moreover, we uncover an unexpected function of the A-C linker in centriole duplication through torus regulation, underscoring the interplay between these protein modules.